Increasing prevalence of asthma diagnosis and symptoms in children is confined to mild symptoms. Issue 4 (1st April 2001) - Kwong, G Ng Man; Proctor, A; Billings, C; Duggan, R; Das, C; Whyte, M K B; Powell, C V E; Primhak, R
Abstract : BACKGROUND: The prevalence of childhood asthma is increasing but few studies have investigated trends in asthma severity. We investigated trends in asthma diagnosis and symptom morbidity between an eight year time period in a paired prevalence study. METHODS: All children in one single school year aged 8–9 years in the city of Sheffield were given a parent respondent questionnaire in 1991 and 1999 based on questions from the International Survey of Asthma and Allergy in Children (ISAAC). Data were obtained regarding the prevalence of asthma and wheeze and current (12 month) prevalences of wheeze attacks, speech limiting wheeze, nocturnal cough and wheeze, and exertional symptoms. RESULTS: The response rates in 1991 and 1999 were 4580/5321 (85.3%) and 5011/6021 (83.2%), respectively. There were significant increases between the two surveys in the prevalence of asthma ever (19.9% v 29.7%, mean difference 11.9%, 95% confidence interval (CI) 10.16 to 13.57, p<0.001), current asthma (10.3% v 13.0%, mean difference 2.7%, 95% CI 1.44 to 4.03, p<0.001), wheeze ever (30.3% v 35.8%, mean difference 5.7%, 95% CI 3.76 to 7.56, p<0.001), wheeze in the previous 12 months (17.0% v 19.4%, mean difference 2.5, 95% CI 0.95 to 4.07, p<0.01), and reporting of medication use (16.9% v 20%, mean difference 3.0%, 95% CI 1.46 to 4.62, p<0.001). There were also significant increases in reported hayfever and eczema diagnoses. CONCLUSIONS: Diagnostic labelling of asthma and lifetime prevalence of wheeze has increased. The current 12 month point prevalence of wheeze has increased but this is confined to occasional symptoms. The increased medication rate may be responsible for the static prevalence of severe asthma symptoms. The significant proportion of children receiving medication but reporting no asthma symptoms identified from our 1999 survey suggests that some children are being inappropriately treated or overtreated.